Communication on the university library websites and students’ scientific information-seeking during the Covid-19 outbreak: A comparison of four Asian countries - Kriyantono, Rachmat; Nirwana, Maya Diah; Tamitiadini, Dian; Handayani, Sri; Destrity, Nia Asthon; Alfira, Nisa; Nugraha, Reza (Universitas Muhammadiyah Ponorogo, 2024)
This studyaims to evaluate the quality of dialogic communication on university library websites and its correlation with students’ scientific information-seeking behaviour during the Covid-19 outbreak. Internet services that organizations frequently use for communicating with their audiences can provide discussion forum services. The university library’s management can investigate their students’ novel ideas, needs, and doubts through dialogic communication, so it will activate and enhance the intellectual power. This research proposed dialogic communication from a sample of 171 undergraduate and graduate students from four countries, China, Indonesia, Taiwan, and Malaysia. Data was obtained by an online survey. The results confirm that during the outbreak, the library websites have implemented the principles of dialogic communication. There is a significant correlation between dialogic communication and scientific information-seeking behaviour except for Chinese students. Library websites can serve as an effective conduit for engaging students in seeking scientific information for academic works. Students stated that e-learning increases their satisfaction and commitment to university websites. Lecturers are recommended to develop collaborative activities among students using the library website. Impacts on practice or policy are that website administrators can use dialogic communication to assist students; university top management can assure students’ rights to education; lecturers may use library website facilities to support asynchronous case-based learning.